THE ICHNOGENUS ENTOBIA FROM THE MIOCENE, PLIOCENE AND PLEISTOCENE OF SOUTHERN ITALY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The taxonomy ef the ichnogenus Entobia Bronn, 1837 is investigated on the basis of Miocene, Pliocene and Pleistocene material from localities in Puglia (Italy). The ichnospecies of Entobia generally may be ascribed to the work of boring sponges; a survey of the twenty—three ichnospecies hitherto erected indicates that only six of these may be regarded as valid. Of these, Entobia megastoma (Fischer) and E. paradoxa (Fischer) occur in the Italian material. In addition to these, six new ichnospecies are erected: E. cateniformis, E. geometrica, E. laquea, E. mammillata, E. ovula, E. volzi.
Keywords: Trace fossils; Taxonomy; Entobia; Sponge boring; Miocene—Pleistocene; Puglia—Italy.